Mastering Digital Personas: Balancing Social Connectivity and Privacy for Tanzanian Adolescents' Well-Being - Nyamwesa, Aloyce M (Indonesian Journal of Social Research (IJSR), 2024)
The rise of social media has transformed digital platforms into essential arenas for public discourse, allowing extensive user participation in content creation and modification. This shift enhances interaction and expression but also presents challenges in digital identity management, particularly regarding reputational integrity and information privacy. This study assesses the impact of digital persona management on the well-being and interpersonal development of Tanzanian adolescents aged 14 to 22. A mixed-methods approach, the research combines quantitative data analysis with qualitative structured interviews to gather insights from a diverse group of social media users. One hundred fifty teenagers were surveyed about their online activities and overall well-being, and five focus groups with 40 participants were conducted for deeper perspectives. Results revealed that social media is a double-edged sword for teenagers, offering significant benefits and risks based on personal characteristics and usage habits. While social media can enhance social connectivity and self-expression, it also poses threats such as cyberbullying, privacy breaches, and unhealthy social comparisons, negatively affecting adolescents' mental health and social relationships. The study underscores the need for comprehensive digital literacy programs that promote responsible social media use and suggests integrating digital persona management into educational curricula to boost adolescents' resilience against adverse impacts. Additionally, it calls for policies to protect young users' privacy and ensure safe online environments. This research contributes to digital identity management theory. It offers practical recommendations for educators, parents, and policymakers, emphasizing the importance of ongoing research to adapt to the evolving digital landscape and safeguard adolescent well-being